Unraveling the relationship between the renin–angiotensin system and endometrial cancer: a comprehensive review - Khan, Nihad Ashraf; Elsori, Deena; Rashid, Gowhar; Tamanna, Sonia; Chakraborty, Ananya; Farooqi, Adeeba; Kar, Ayman; Sambyal, Niti; Kamal, Mohammad Azhar (Frontiers in Oncology, 2023)
Endometrial cancer, the most common adenocarcinoma represents 90% of uterine cancer in women with an increased incidence of occurrence attributed to age, obesity, hypertension, and hypoestrogenism. Being the most common gynecological malignancy in women it shows a relation with the activation of different components of the renin-angiotensin system (RAS), predominantly involved in maintaining blood pressure, salt, water, and aldosterone secretion.Thereby, playing a significant role in the etiology of hypertension. The expression of the components of the RAS i.e ACE-I, ACE-II, AT1R, AT2R, and Pro(renin) receptor are widely expressed in both glandular and stromal cells of the endometrium with varying levels throughout the different phases of the menstrual cycle. This causes the endometrial reninangiotensin system (RAS) to implicate angiogenesis, neovascularization, and cell proliferation. Thus, dysfunctioning in the endometrial (RAS) could predispose the growth and spread of EC. Interestingly, increased expression of AngII, AGTR1, and AGTR2 showed advancement in the stages and progression of EC via prorenin/ATP6AP2 and AngII/AGTR1 pathway. Therefore, this review corresponds to unraveling the relationship between the progression and development of endometrial cancer with the dysfunction in the expression of various components associated with RAS in maintaining blood pressure.